Border town issues in tourism development: the case of Perlis, Malaysia - Goh, Hong Ching; Tan, Wan Hin; Ching, Fei Ern (Faculty of Social Sciences and Humanities, UKM,Bangi, 2014)
This paper discusses the state of tourism development in Perlis the smallest state in the country located at the northernmost part of Peninsular Malaysia where Malaysia borders Thailand . The focus is on the issues and challenges faced in developing tourism in the state. The collection of both quantitative and qualitative data was carried out in February and November 2010 involving site inventory, interviews, literature survey and desktop search. The findings reveal that despite the state’s tourism potentials poor accessibility, improper and inappropriate development planning not in accordance to the uniqueness of local tourism resources, and poor maintenance have thwarted the potential role of tourism as a tool of development in the state, thus limiting its tourism function to that of a mere transit town and a minor border tourism destination.